The Effect of STEM-Based Discovery Learning Model on Critical Thinking Skills of Elementary School Students on Fraction Topics in the Context of Islamic Education - Wahyuningtyas, Indah Noviani; Widiyono, Aan (Universitas Muhammadiyah Magelang, 2024)
This study examines the effect of the STEM-based Discovery Learning model on improving students' critical thinking skills in fraction material in the context of Islamic education. This kind of study is a mixed-method quantitative experiment with a sequential explanatory design. This study involved 4th grade students of SD Negeri 3 Karanggondang. The instruments used were tests and interviews. The results of the statistical analysis showed that the application of this model resulted in a significant increase in students' critical thinking skills, with a large effect on the aspects of concept analysis and evaluation. The implications of this study confirm that the STEM-based Discovery Learning model is not only effective in improving cognitive skills but is also in line with Islamic values ​​that encourage curiosity, problem solving, and critical reflection. The benefit of this study for elementary education, especially in Islamic education, is in the potential of this model to help shape the critical thinking skills needed to face modern challenges. This model offers an innovative approach that aligns with the Islamic curriculum, enabling students to connect scientific concepts with Islamic values ​​holistically.